Global and regional prevalence, burden, and risk factors for carotid atherosclerosis: a systematic review, meta-analysis, and modelling study - Song, S; Fang, Z; Wang, H; Cai, Y; Rahimi, K; Zhu, Y; Fowkes, FGR; Fowkes, FJI; Rudan, I (Elsevier, 2020)
Background Estimation of the epidemiological burden of carotid atherosclerosis can serve as a basis for prevention and management of cardiovascular disease. We aimed to provide the first estimation on the prevalence, number of cases, and risk factors for carotid atherosclerosis in the general population globally and regionally. Methods In this systematic review, meta-analysis, and modelling study, we searched PubMed, MEDLINE, Embase, Global Health, and China National Knowledge Infrastructure for articles published from database inception until May 7, 2019, with no language restrictions, for population-based studies that quantified prevalence of carotid atherosclerosis by means of increased carotid intima-media thickness, carotid plaque, and carotid stenosis. Studies were eligible if they included bilaterally scanned carotid arteries using ultrasonography and defined increased carotid intima-media thickness as a thickness of 1·0 mm or more, carotid plaque as a focal carotid intima-media thickness of 1·5 mm or more encroaching into the lumen or at least 0·5 mm or 50% compared with the surrounding carotid intima-media thickness values, and carotid stenosis as 50% or more stenosis. Studies were excluded if the sample was not representative of the general population. We also included studies identified in our previous systematic review and meta-analysis of the prevalence of carotid atherosclerosis in China. We estimated age-specific and sex-specific prevalences of increased carotid intima-media thickness, carotid plaque, and carotid stenosis. We used UN population data to generate the number of people affected in 2000, 2015, and 2020. We did random-effects meta-analyses to assess the effects of risk factors for increased carotid intima-media thickness and carotid plaque. We derived regional numbers of people living with increased carotid intima-media thickness and carotid plaque in 2015 using a risk factors-based model by WHO region. All analyses were done in populations aged 30–79 years due to availability of data. This systematic review and meta-analysis is registered online on PROSPERO, CRD42019134709. Findings We identified 8632 articles through our database search, of which 515 were eligible for full-text review, including 37 articles from our previous study, and 59 articles were eligible for inclusion in our systematic review and meta-analysis. Overall, in people aged 30–79 years in 2020, the global prevalence of increased carotid intima-media thickness is estimated to be 27·6% (95% CI 16·9–41·3), equivalent to 1066·70 million affected people and a percentage change of 57·46% from 2000; of carotid plaque is estimated to be 21·1% (13·2–31·5), equivalent to 815·76 million affected people and a percentage change of 58·97% from 2000; and carotid stenosis is estimated to be 1·5% (1·1–2·1), equivalent to 57·79 million affected people and a percentage change of 59·13% from 2000. The prevalence of increased carotid intima-media thickness, carotid plaque, and carotid stenosis increased consistently with age and was higher in men than in women. Current smoking, diabetes, and hypertension were common risk factors for increased carotid intima-media thickness and carotid plaque. In 2015, the Western Pacific region had the largest share of global cases of increased carotid intima-media thickness (317·62 million [33·36%] of 952·13 million affected people) and carotid plaque (240·77 million [33·20%] of 725·25 million), whereas the African region had the smallest share of cases of increased carotid intima-media thickness (59·08 million [6·21%]) and the Eastern Mediterranean region had the smallest share of carotid plaque cases (44·59 million [6·15%]). Interpretation A substantial global burden of carotid atherosclerosis exists. Effective strategies are needed for primary prevention and management of carotid atherosclerosis. High-quality epidemiological investigations on carotid atherosclerosis are needed to better address the global burden of carotid atherosclerosis at finer levels. Funding None.